2012
DOI: 10.1074/jbc.m112.377218
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Mitogen-activated Protein Kinase (MAPK) Pathway by FGF Receptor 3 (FGFR3)/Ras Mediates Resistance to Vemurafenib in Human B-RAF V600E Mutant Melanoma

Abstract: Background: B-RAF V600E melanomas rapidly develop resistance to B-RAF inhibitors in the clinic. Results: FGFR3/Ras signaling is elevated and induces resistance to vemurafenib in vemurafenib-resistant cells. Conclusion: FGFR3/Ras confers resistance to B-RAF inhibition via MAPK pathway reactivation. Significance: A novel mechanism of resistance to B-RAF inhibitors is described and potential therapeutic strategies are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
144
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(151 citation statements)
references
References 36 publications
5
144
0
1
Order By: Relevance
“…Other reports have also suggested that FGFR3 activation mediates resistance to cetuximab in wild-type squamous tumor cells with KRAS mutations and to vemurafenib in BRAF V600E melanoma cells ( 62,63 ).…”
Section: Fgf and Drug Resistancementioning
confidence: 99%
“…Other reports have also suggested that FGFR3 activation mediates resistance to cetuximab in wild-type squamous tumor cells with KRAS mutations and to vemurafenib in BRAF V600E melanoma cells ( 62,63 ).…”
Section: Fgf and Drug Resistancementioning
confidence: 99%
“…A375R1, A375R3, M14R, and SH4R cells were generated by treating their respective parental cells with gradually increasing concentrations of vemurafenib, up to 2 mmol/L as described previously (10). The resistant mechanism of A375R1, A375R3, and M14R cells was associated with RTK/RAS activation and MAPK reactivation (10).…”
Section: Development Of Vemurafenib-resistant Cell Linesmentioning
confidence: 99%
“…A375R1, A375R3, M14R, and SH4R models with acquired resistance to vemurafenib were generated by treating respective parental cells with gradually increasing concentrations of vemurafenib, up to 2 mmol/L, as previously described (10). A375R2 cells were generated by treating A375 cells with a high concentration of vemurafenib (2 mmol/L) for 1 week, followed by culturing with vemurafenib (1 mmol/L) for up to 20 passages.…”
Section: Generation Of Vemurafenib-resistant Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations